Truth processes and decolonial transformation: a comparative view of Guatemala, Peru, Chile and Colombia. - Ramos-Cortez, Carola; MacNeill, Timothy (Third World Quarterly, 2024)
This article explores periods of transformative politics in Guatemala, Peru, Chile and Colombia – states that have undergone processes of truth involving Indigenous peoples and have opted for multicultural neoliberal politics. We revisit the idea of decolonial transformation as an ongoing, unfinished process, while refining a framework of four factors that facilitate decoloniality. These factors include: (1) a process of truth or peace; (2) Indigenous leadership with a commitment to community participation; (3) the transfer of administrative autonomy over Indigenous governance and service provision; and (4) redistributive measures that favour Indigenous peoples. This framework is analysed and refined by bringing critiques of reconciliation politics from Indigenous resurgence scholars and decoloniality theories from Latin America into dialogue, and then analysing the above-mentioned Latin American case studies. We argue that processes of truth can open space for decoloniality, but only in circumstances where the strength of the three other factors contributes to the transcendence of neoliberal recognition politics.